Velocity encoded mitral valve inflow cine: A novel and more reproducible method to determine cardiac rest periods during coronary magnetic resonance angiography. (March 2022) - Markus, Richard; Tandon, Animesh; Fares, Munes; Dillenbeck, Jeanne; Greil, Gerald F.; Batsis, Maria; Greer, Joshua; Potersnak, Amanda; Zhang, Song; Hussain, Tarique; Avula, Sravani
A high temporal resolution, 4-chamber (4CH) cine is the standard method for determining cardiac rest periods during whole heart coronary magnetic resonance angiography (CMRA). We evaluated the image quality and reproducibility between the 4CH cine method and a novel approach using a velocity encoded mitral valve inflow cine (MVI). The goal of this study was to compare the quality of CMRAs utilizing MVI versus 4CH methods. Sharpness and vessel length for the LCA and RCA using each method were determined using Soap Bubble and two blinded observers independently assessed coronary image quality. Offline analysis on a separate, retrospective cohort (n = 25) was used to compare MVI and 4CH reproducibility. In the prospectively evaluated cohort there was no difference in overall vessel sharpness (4CH vs MVI mean ± SD) (31.0 ± 5.5% vs 30.5 ± 5.7%, p  = .63), LCA vessel sharpness (30.0 ± 5.4% vs 31.1 ± 8.2%, p  = .44), LCA length (4.7 ± 1.4 cm vs 4.6 ± 1.6 cm, p  = .66), RCA vessel sharpness (32.1 ± 6.9% vs 31.1 ± 7.7%, p  = .55), RCA length (5.51 ± 2.6 cm vs 5.95 ± 2.4 cm, p  = .38), or image quality rating (2.66 vs 2.62, p  = .80) between methods. In the retrospective cohort, the MVI method had 5.4% lower inter-observer variability (95% CI 3.7, 7.2%, p  < .0001) and 3.9% lower intra-observer variability (95% CI 2.4, 5.4%, p  < .0001) than the 4CH method. MVI is a technically feasible and more reproducible method to determine cardiac rest periods compared to 4CH while preserving vessel sharpness, vessel length & image quality.